Cytotoxic and genotoxic effects of mercury in house fly Musca domestica (Diptera: Muscidae) - Mishra, N.; Tewari, R. R. (Cellular and Molecular Biology, 2011)
Mercury, one of the most widely diffused and hazardous environmental contaminants, induces oxidative stress in organisms, which ultimately leads to genotoxicity and cytotoxicity. House fly Musca domestica L. was used as a model for assaying the genotoxic potential of mercury with the help of micronucleus assay, chromosomal aberration assay as end points and cytotoxicity by assaying the mitotic index and the extent of tissue damage by trypan blue dye exclusion. Late third instar larvae were exposed to different dietary concentrations of mercury (0.0001 mg/ml- 10 mg/ml) for various time intervals. A dose dependent increase in chromosomal aberrations, micronucleus frequency and mitotic index was observed. Micronucleus frequency increases with time while mitotic index decreases showing decreasing rate of cell proliferation due to an increase in cell death. Trypan blue staining gives the visual manifestation of cytotoxicity at higher concentrations of mercury (1 mg/ml- 10mg/ml). The present study suggests that the house fly model may be used to assay the genotoxicity and cytotoxicity of mercury as well as other environmental pollutants.